2017
DOI: 10.1071/an16068
|View full text |Cite
|
Sign up to set email alerts
|

Production responses of reproducing ewes to a by-product-based diet inoculated with the probiotic Bacillus amyloliquefaciens strain H57

Abstract: The potential application of the spore-forming probiotic Bacillus amyloliquefaciens strain H57 (H57) as a novel probiotic for ruminants was evaluated in reproducing ewes. Performance responses were determined by delivering H57 in a pelleted diet based mainly on palm kernel meal (PKM) and sorghum grain. PKM is an agro-industrial by-product with a reputation for poor palatability and the availability of the starch in sorghum grain can be limited in ruminants. The hypothesis was that H57 improves the feeding valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 33 publications
3
39
0
Order By: Relevance
“…This could lead to the increased weight gain observed in the H57 fed sheep. The H57 fed sheep also showed an overall increased expression of enzymes involved in glycolysis, suggesting an increased conversion of sugars into energy substrates such as VFAs.However, as Le et al (2016b) observed, total VFA concentration was not higher in the H57 fed sheep, but in fact was significantly lower (P = 0.02) than the control ewes.The findings of this study suggest that the addition of H57 to pelleted feed stimulates rumen microbial populations to express greater quantities of hemicellulolytic and glycolysis pathway enzymes, compared to those in animals fed the control feed. As the feed is more efficiently digested, the host is able to utilise the resultant energy substrates for growth and development.…”
mentioning
confidence: 63%
See 4 more Smart Citations
“…This could lead to the increased weight gain observed in the H57 fed sheep. The H57 fed sheep also showed an overall increased expression of enzymes involved in glycolysis, suggesting an increased conversion of sugars into energy substrates such as VFAs.However, as Le et al (2016b) observed, total VFA concentration was not higher in the H57 fed sheep, but in fact was significantly lower (P = 0.02) than the control ewes.The findings of this study suggest that the addition of H57 to pelleted feed stimulates rumen microbial populations to express greater quantities of hemicellulolytic and glycolysis pathway enzymes, compared to those in animals fed the control feed. As the feed is more efficiently digested, the host is able to utilise the resultant energy substrates for growth and development.…”
mentioning
confidence: 63%
“…However, as Le et al (2016b) observed, total VFA concentration was not higher in the H57 fed sheep, but in fact was significantly lower (P = 0.02) than the control ewes.…”
mentioning
confidence: 63%
See 3 more Smart Citations